Antigonos “Monophthalmos”: Some Particulars in the Interpretation of the Nickname - Gabelko, Oleg L. (Anabasis. Studia Classica et Orientalia, 2016)
The article is concerned with the analyses of the unofficial epithets of Antigonos I, who is known first of all as Monophthalmos – the One-Eyed (Hieronym. F. 34 = Ps.-Luc. Macrob. 11, 13; Polyb. V.67.7). According to the author’s point of view, Antigonos initially was surnamed Ἑτερόφθαλμος after heavy injury deprived him of the eye during the siege of Perinthos in 340 BC. But after the improper story with the organizing by king (at some moment after 306 BC) of the murder of his enemy, philosopher Theocritos of Chios, who named Antigonos with scoffing alias ‘The Cyclops’ (Plut. Mor. 11b; 633c; Ael. Var. Hist. XII. 43; cf. Macrob. Sat. VII. 3. 12), he received new nickname Μονόφθαλμος, which, unlike of semantically neutral Ἑτερόφθαλμος, is connected in many sources namely with the Cyclopes and was applied to no one-eyed historical persons for the exception of Antigonos I.